"La terre est notre vie": La relation des Toba du Gran Chaco à leur territoire - Tola, Florencia Carmen (2014)
In the last two decades, the Argentine Chaco has been transformed into a land given over to the expansion of the soy border. As evidence of an aggressive policy of regional development, the process has gone along with an accelerating dyanmic of deforestation, an alteration of the ecosystem, the migration of the rural population, and repeated attempts to expel the indigenous communities. This article focuses on the tensions and the current political and environmental contradictions involved in these mutations. It addresses the question of the relations linking the toba (qom) communities to their lands and resources, and the effects on these communities of an extractivist model of development, implemented by left-leaning governments. Far from the exotic figure of an ecological Indian, the conceptions of life and of land fostered by the qom community are actually part of a specific ontology, in rupture with the dominant productivist and extractivist model.